2021
DOI: 10.1007/s10071-021-01516-1
|View full text |Cite
|
Sign up to set email alerts
|

Irrational risk aversion in an ant

Abstract: Animals must often decide between exploiting safe options or risky options with a chance for large gains. Both proximate theories based on perceptual mechanisms, and evolutionary ones based on fitness benefits, have been proposed to explain decisions under risk. Eusocial insects represent a special case of risk sensitivity, as they must often make collective decisions based on resource evaluations from many individuals. Previously, colonies of the ant Lasius niger were found to be risk-neutral, but the risk pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Examining the results of the aforementioned model, we discovered a possible contrast effect, as depending on the condition, the amount of pheromone deposited for the same treatment changed abruptly. It is indeed crucial to consider how the first experience of ants can have ripple effect on its subsequent decisions (De Agrò et al, 2021). To further examine this effect we remodeled the data including the first experienced treatment as a factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examining the results of the aforementioned model, we discovered a possible contrast effect, as depending on the condition, the amount of pheromone deposited for the same treatment changed abruptly. It is indeed crucial to consider how the first experience of ants can have ripple effect on its subsequent decisions (De Agrò et al, 2021). To further examine this effect we remodeled the data including the first experienced treatment as a factor.…”
Section: Discussionmentioning
confidence: 99%
“…The “liking” vs “wanting” distinction however, especially given the results observed in this experiment, suggests that perception and memory can be segregated process. Most experiments recording both pheromone deposition and subsequent choice use food quality (from high concentration sucrose to distasteful solutions) as the measured unit (De Agrò et al, 2021; Oberhauser and Czaczkes, 2018; Wendt et al, 2019). Logarithmic perception of quality is probably the reason mismatch a mismatch between choice and instantaneous value perception has eluded discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the results of the aforementioned model, we discovered a possible contrast effect, as depending on the condition, the amount of pheromone deposited for the same treatment changed abruptly. It is indeed crucial to consider how the first experience of ants can have ripple effect on its subsequent decisions ( De Agrò et al, 2021 ). To further examine this effect we remodelled the data including the first experienced treatment as a factor.…”
Section: Methodsmentioning
confidence: 99%
“…from 0.5 to 1.5 molar). Recently, De Agrò et al, 2021 , demonstrated that Lasius niger ants have a strong aversion to risky food sources (i.e. with fluctuating quality), which could be fully explained by logarithmic value perception, as predicted by prospect theory.…”
Section: Introductionmentioning
confidence: 98%